Firearm-Related Laws in All 50 US States, 1991–2016 - Siegel, Michael; Pahn, Molly; Xuan, Ziming; Ross, Craig S.; Galea, Sandro; Kalesan, Bindu; Fleegler, Eric; Goss, Kristin A. (American journal of public health (1971), 2017)
Objectives. To describe a new database containing detailed annual information on firearm-related laws in place in each of the 50 US states from 1991 to 2016 and to summarize key trends in firearm-related laws during this time period. Methods. Using Thomson Reuters Westlaw data to access historical state statutes and session laws, we developed a database indicating the presence or absence of each of 133 provisions of firearm laws in each state over the 26-year period. These provisions covered 14 aspects of state policies, including regulation of the process by which firearm transfers take place, ammunition, firearm possession, firearm storage, firearm trafficking, and liability of firearm manufacturers. Results. An examination of trends in state firearm laws via this database revealed that although the number of laws nearly doubled during the study period, there was substantial heterogeneity across states, leading to a widening disparity in the number of firearm laws. Conclusions. This database can help advance firearm policy research by providing 26 years of comprehensive policy data that will allow longitudinal panel study designs that minimize the limitations present in many previous studies.